2020
DOI: 10.1111/oik.07567
|View full text |Cite
|
Sign up to set email alerts
|

The degree of spatial variation relative to temporal variation influences evolution of dispersal

Abstract: In the face of ongoing global climate and land use change, organisms have multiple possibilities to cope with the modification of their environment. The two main possibilities are to either adapt locally or disperse to a more suitable habitat. The evolution of both local adaptation and dispersal interacts and can be influenced by the spatial and temporal variation (of e.g. temperature or precipitation). In an individual based model (IBM), we explore evolution of phenotypes in landscapes with varying degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Lower body sizes also increase reproductive rates (Savage et al 2004) and thus more offspring dispersal can take place, further assisting species to respond environmental change via dispersal (Berg et al 2010). Additionally, theoretical evidence has suggested that environmental fluctuations may select for intraspecific variation of dispersal ability (Mathias et al 2001, Sieger and Hovestadt 2020), constituting bet‐hedging strategies. Fluctuating environment may also select for increased niche tolerances to cope with varying conditions (Lynch and Gabriel 1987, Holt 1990), although this might be mostly relevant for larger species (due to longer generation times) and poor dispersers (reviewed by Sexton et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lower body sizes also increase reproductive rates (Savage et al 2004) and thus more offspring dispersal can take place, further assisting species to respond environmental change via dispersal (Berg et al 2010). Additionally, theoretical evidence has suggested that environmental fluctuations may select for intraspecific variation of dispersal ability (Mathias et al 2001, Sieger and Hovestadt 2020), constituting bet‐hedging strategies. Fluctuating environment may also select for increased niche tolerances to cope with varying conditions (Lynch and Gabriel 1987, Holt 1990), although this might be mostly relevant for larger species (due to longer generation times) and poor dispersers (reviewed by Sexton et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This results in a landscape community that is less rich overall but also less globally dominated by a small number of highly abundant species. Due to their larger population sizes and the bet-hedging opportunities afforded by a spatially heterogeneous environment, these populations are likely to survive extreme environmental fluctuations (Sieger & Hovestadt, 2020), resulting in a more stable landscape community composition in the long term. As with all models, our model makes a number of simplifying assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we attempt to address this gap using a spatially explicit, using an individual-based metacommunity model implemented in Julia 1.1.1 (Bezanson et al, 2012) based on the model of Sieger and Hovestadt (2020) to systematically explore the effects of landscape structure on patterns of species richness and diversity via their…”
Section: Introductionmentioning
confidence: 99%
“…Overall, our experiences with the language have been almost entirely positive (e.g. Leidinger et al, 2021;Sieger & Hovestadt, 2020;Vedder et al, 2020).…”
Section: Choosing a Languagementioning
confidence: 94%